A systematic review of factors influencing students’ behavioral intention to adopt online homework - Chen, Liu; Wong, Su Luan; How, Shwu Pyng (Springer, 2023)
As a format of homework delivery, online homework promises the usage of technology to help students learn better in the modern era. However, evidence has shown that many students are reluctant to adopt online homework for learning. Behavioral intention is acknowledged as a critical factor predicting the adoption of technology among users. Relevant studies targeted specifically on online homework in terms of behavioral intention are scattered till now. Thus, a review of the literature was conducted to identify factors influencing students’ behavioral intention to adopt online homework. Abiding by the inclusion and exclusion criteria with the guide of PRISMA, 25 articles were selected from four databases. In the current study, the included studies’ characteristics were outlined first. Then, based on the UTAUT model, the findings showed that performance expectancy, effort expectancy, social influence, and facilitating conditions impact students’ behavioral intention to adopt online homework. Other factors, such as content design, functions, attitudes, and so on, are also associated with students’ behavioral intention to adopt online homework. Further studies and limitations are also included in this study.